1986
DOI: 10.1111/j.1651-2227.1986.tb10401.x
|View full text |Cite
|
Sign up to set email alerts
|

Ductus Closure in Preterm Infants Effects on Cerebral Hemodynamics

Abstract: ABSTRACT. Idracranial arterial blood flow velocities were studied before and after ductus closure by smgery (n=8) and indomethacin (n=10) in very low birth weight infants. Blood flow velocities were measured non‐invasively through the fontanel with a pulsed Doppler velocimeter. Ligation of the ductus was associated with a 62% increase in mean flow velocity 24 hours after surgery, mainly secondary to increased diastolic flow velocity. Iodomethacin (0.2 nig/kg i.v.) induction of ductus constriction was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…As confirmed by previous literature [1,15,24,25] , we found significantly increased rSO 2 values after PDA ligation (72 8 7% by 24 h). This change likely reflects a low baseline rSO 2 and subsequent normalization of cerebral oxygenation, with post-ligation levels comparable to the mean rSO 2 in control infants without a hsPDA (69 8 4%).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As confirmed by previous literature [1,15,24,25] , we found significantly increased rSO 2 values after PDA ligation (72 8 7% by 24 h). This change likely reflects a low baseline rSO 2 and subsequent normalization of cerebral oxygenation, with post-ligation levels comparable to the mean rSO 2 in control infants without a hsPDA (69 8 4%).…”
Section: Discussionsupporting
confidence: 81%
“…However, consequences of this rapid change in cerebral oxygenation are unclear. A sustained increase in rSO 2 after PDA ligation implies increased cerebral blood flow, as transcranial Doppler ultrasound studies have demonstrated [24,26] . In contrast to our findings, two studies found unchanged or decreased rSO 2 after PDA ligation [14,27] .…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest an age-dependent shift in the primary endothelial-dependent dilator mechanism of the human vertebral artery from prostanoid to NO. Numerous studies in premature human infants suggest a high sensitivity of the cerebral circulation, particularly hypercapnia responsiveness, to the COX inhibitor indomethacin (21)(22)(23)26). Data from human infant cerebral arteries in vitro suggest that generation of NO in response to calcium ionophore is markedly reduced in the human infant compared with newborn lambs (27).…”
Section: Discussionmentioning
confidence: 99%
“…The decision to administer indomethacin should be carefully considered in terms of riskbenefit ratio, given its potential adverse effects on cerebral 42,43 and/or mesenteric blood flow. 44 As renal perfusion, glomerular filtration rate and diuresis in early neonatal life strongly depend on the vasodilator effects of prostaglandins on the afferent glomerular arterioles, indomethacin and ibuprofen, as other cyclo-oxygenase inhibitors may not be exempt from some renal undesirable effects.…”
Section: Ductal Steal and Nonsteroidal Anti-inflammatory Agentsmentioning
confidence: 99%